2014
DOI: 10.1016/j.bcp.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific recycling of tetrahydrobiopterin by dihydrofolate reductase explains differential effects of 7,8-dihydrobiopterin on endothelial nitric oxide synthase uncoupling

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Thereby, these findings suggest that pro-inflammatory stimuli in microglial cells promote a stronger capacity for dopamine biosynthesis in animal models. However, it is important to keep in mind that human cells are less efficient generating BH4 in comparison to other species (Schmidt et al, 2014).…”
Section: Dopaminergic Regulation Of Microglial Cellsmentioning
confidence: 99%
“…Thereby, these findings suggest that pro-inflammatory stimuli in microglial cells promote a stronger capacity for dopamine biosynthesis in animal models. However, it is important to keep in mind that human cells are less efficient generating BH4 in comparison to other species (Schmidt et al, 2014).…”
Section: Dopaminergic Regulation Of Microglial Cellsmentioning
confidence: 99%
“…Hence, low Arg can lead not only to low endothelial/vascular NO due to substrate deficiency but also due to increased oxidation of NO to peroxynitrites, and downstream to that, oxidation of the eNOS cofactor (6 R )‐5,6,7,8‐tetrahydro‐ l ‐biopterin (BH4) . The resulting accumulation of oxidation products such as 6,7‐[8H]‐H2‐biopterin (BH2) leads to eNOS uncoupling, such that this enzyme produces superoxides rather than NO …”
Section: Introductionmentioning
confidence: 99%
“…13 The resulting accumulation of oxidation products such as 6,7-[8H]-H2-biopterin (BH2) leads to eNOS uncoupling, such that this enzyme produces superoxides rather than NO. [14][15][16] Increased ADMA can reduce NO bioavailability 17 and further increase oxidative stress, thus impairing both insulin sensitivity and vascular function. 18 Although several reports support the notion that circulating ADMA is increased in individuals with diabetes, [19][20][21][22] this has not been observed uniformly, 23,24 suggesting possible confounding effects of coexisting conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Schmidt et al ., [30] confirmed this hypothesis by showing that HUVECs exhibit basal BH 4 levels of 0.3 pmol/mg, and as a consequence, eNOS may not be fully coupled. When we analyzed the eNOS dimer/monomer ratio in HUVECs under basal conditions, we observed that eNOS exists primarily as dimers (Figure 2B) and that addition of BH 4 did not have a statistically significant effect on dimerization (Figure 4B).…”
Section: Discussionmentioning
confidence: 93%